Differential expression of alarmins—S100A9, IL-33, HMGB1 and HIF-1α in supraspinatus tendinopathy before and after treatment. Issue 1 (31st May 2017) - Mosca, Michael J; Carr, Andrew J; Snelling, Sarah J B; Wheway, Kim; Watkins, Bridget; Dakin, Stephanie G
Abstract : Background: Alarmins, endogenous molecules released on tissue damage have been shown to play an important role in inflammatory musculoskeletal conditions including fracture repair andrheumatoid arthritis. However, the contribution of alarmins to the pathogenesis of tendon disease is not fully understood. Methods: We investigated expression of alarmin proteins (S100A9, high-mobility group box 1 (HMGB1) and interleukin-33 (IL-33) and hypoxia-inducible factor 1α (HIF-1α), a subunit of an oxygen sensitive transcription factor, in three cohorts of human supraspinatus tissues: healthy (n=6), painful diseased (n=13) and post-treatment pain-free tendon samples (n=5). Tissue samples were collected during shoulder stabilisation surgery (healthy) or by biopsy needle (diseased/treated). Immunohistochemistry was used to investigate the protein expression of these factors in these healthy, diseased and treated tendons. Kruskal-Wallis with pairwise post hoc Mann-Whitney U tests were used to test for differences in immunopositive staining between these tissue cohorts. Additionally, costaining was performed to identify the cell types expressing HIF-1α, S100A9, IL-33 and HMGB1 in diseased tendons. Results: Immunostaining showed HIF-1α and S100A9 were increased in diseased compared with healthy and post-treatment pain-free tendons (p<0.05). IL-33 was reduced in diseased compared with healthy tendons (p=0.0006). HMGB1 was increased in post-treatment pain-free compared with healthy and diseased tendons (p<0.01). Costaining of diseased tendon samples revealed that HIF-1α, S100A9 and IL-33 were expressed by CD68+ and CD68− cells, whereas HMGB1 was predominantly expressed by CD68− cells. Conclusions: This study provides insight into the pathways contributing to the progressionand resolution of tendon disease. We found potential pro-inflammatory and pathogenic roles for HIF-1α and S100A9, a protective role fornuclear IL-33 and a potentially reparative function for HMGB1 in diseased supraspinatus tendons.